Synthesis of Molecularly Imprinted Membrane Glucose for Selective Membrane Transport - Muhammad Cholid Djunaidi; Henita Saulia Utari; Khabibi Khabibi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Molecularly Imprinted Membrane (MIM) was synthesized using polyeugenoxy acetic acid as the functional polymer, polyethylene glycol as the crosslinker agent, and polysulfone as a base membrane which was applied as a selective glucose membrane transport, and the immersion time expected to determine the transport capability of the membrane. This study aimed to determine the selectivity and transport properties of the MIM and NIM membranes. NIM was used as a control for MIM to research the selectivity test. In comparison, MIM has a template, while NIM is without a template. In this study, eugenol derivatives were synthesized through a polymerization reaction using a BF3-diethylether catalyst polymerized for 16 hours to produce polyeugenoxy acetic acid (PA). The PA was contacted with 7500 ppm glucose. PA-glucose produced an imprinted membrane, while PA produced a non-imprinted membrane. The membrane thickness was measured with a micrometer, resulting in a measurement range of 0.08–0.10 mm. The best transport result was achieved at the membrane passage of 24 hours of immersion time because the effect of membrane immersion time can increase the porosity, hydrophilicity, and membrane’s transport ability. Transport with MIM membrane shows better and more selective results than NIM. This confirms the existence of a glucose template on the MIM membrane, which causes the MIM membrane to recognize glucose and transport glucose better than fructose. This study’s advantages include learning how immersion time affects membrane production and determining how well MIM and NIM membranes transport and select glucose and fructose. Furthermore, membrane characterizations were done using FTIR to identify functional groups, SEM-EDX to analyze the shape of the membrane, and a UV-Vis spectrophotometer to analyze the membrane’s selectivity and transport capabilities.